A Pilot Study on the Dual Role of ADAMTS-1, -4, and -5 in Necrotizing Enterocolitis: Linking Tissue Pathology and Serum Biomarker Discovery - Tayman, Cüneyt; Çakır, Ufuk; Yılmaz, Yavuz; Tayman, Mahmure Ayşe; Koyuncu, İsmail (American Journal of Perinatology, 2025)
Necrotizing enterocolitis (NEC) is an inflammatory and destructive disease of the gastrointestinal system, predominantly affecting premature infants. Despite being associated with multifactorial causes, its etiopathogenesis has not yet been clearly elucidated. This study aims to investigate the role of matrix metalloproteinases, particularly the thrombospondin motif-containing proteins ADAMTS-1, -4, and -5, in the pathogenesis of NEC.Intestinal tissue samples were obtained from 31 patients incluiding preterm infants with surgically confirmed NEC. The mRNA expression levels of ADAMTS-1, -4, and -5 were analyzed using RT-qPCR. In addition, immunohistochemical analyses were performed to evaluate the expression of ADAMTS-1, -4, and -5 proteins in tissue samples. Serum levels of these proteins were measured using the ELISA method.RT-qPCR analyses revealed significantly higher expression levels of ADAMTS-1, -4, and -5 in NEC tissue samples compared with the control tissue samples (p < 0.05). Immunohistochemical analysis demonstrated increased expression patterns of these proteins in the NEC group relative to controls (p < 0.05). Furthermore, serum levels of ADAMTS-1, -4, and -5 were found to be elevated in NEC patients (p < 0.05). ROC analysis revealed excellent diagnostic performance of ADAMTS proteins, particularly for ADAMTS-4 (AUC: 1.00), indicating their potential as a non-invasive biomarker for NEC. ADAMTS levels significantly correlated with CRP and IL-6, supporting their involvement in the inflammatory cascade of NEC.The observed upregulation of ADAMTS-1, -4, and -5 in NEC-affected tissues and serum may provide new insights into the disease's pathogenesis and diagnosis. ADAMTS proteins may serve as novel diagnostic biomarkers and therapeutic targets for early identification and treatment of NEC. Targeting members of the ADAMTS protein family could represent a promising therapeutic strategy for the treatment of NEC.
Keywords: necrotizing enterocolitis; matrix metalloproteinases; ADAMTS-1; ADAMTS-4; ADAMTS-5; inflammation; serum biomarkers; premature infants